What we should know about patient safety culture: An empirical investigation of viewpoints from four categories of hospital staffs in Taiwan - Chih-Husan Huang; Hsin-Hung Wu; Yii-Ching Lee; Cheng-Feng Wu; Meng-Chen Lin (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
In recent years, patient safety culture in healthcare organizations has been considered as a critical issue for improving the quality of healthcare. The current study attempts to examine the perceptions of patient safety from four different categories of hospital staffs in a case hospital by conducting the Chinese version of Safety Attitudes Questionnaire, developed from the Taiwan Joint Commission on Hospital Accreditation. Pearson correlation analysis is used to assess the strength and direction of the relationships among seven patient safety culture dimensions. For physicians and administrators, the findings highlight that safety climate is highly correlated to teamwork climate and perceptions of management. For nurses, the results reveal that safety climate is highly correlated to teamwork climate and working conditions. For technicians, job satisfaction is highly related to safety climate and working conditions. Additionally, emotional exhaustion is negatively significant to stress recognition and safety climate for all hospital staff.
Keywords: 330; Safety attitudes questionnaire; Patient safety culture; Hospital staffs; Pearson correlation analysis